The Effect of Workload on Employee Performance with Burnout as a Mediation Variable - Arie Fajriani; Dovi Septiari (Pusat P2M Politeknik Negeri Batam, 2016)
This research is motivated by the many previous studies that examined on the workload and performance of the employees, but not mediated by burnout of employees, so the purpose of this study was to determine and analyze whether burnout mediates the effect of workload on employee performance. This study used a questionnaire which would then be distributed to the employees who work in the manufacturing company in Batam. Population of manufacturing company in Batam is 276 companies. Sampling method using slovin formula, so that the samples used were 163 manufacturing companies in Batam. The study found that burnout mediates most of the effect of work load on employee performance.